Best Answer

By factorising:

x + 9 = x2

x2 - x - 9 = 0

(x - 3.54)(x + 2.54) = 0

x = 3.54, x = -2.54

By the quadratic formula:

x = -(-1) ± √[(-1)2 - 4(1)(-9)]/2(1)

x = 1 ± √(1 - -36)/2

x = 1 ± √37/2

x = 0.5 ± 6.08/2

x = 0.5 + 3.04 = 3.54, x = 0.5 - 3.04 = -2.54

The same solutions are given both ways, which confirms the result.

Q: How do you solve x plus 9 equals x squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x^2 +9 =x^2 -9 9=-9 No solution

A + 9 = 21 A = 21 - 9 A = 12

Yes it is. The thing that makes it a quadratic equation is that "x squared" in there.

Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7

-3

Related questions

x=9 squared

Solve this problem -x squared -40x- 80 =0

X = √63

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

x^2 +9 =x^2 -9 9=-9 No solution

7(3y-2)-(-4y+9)

3

10

A + 9 = 21 A = 21 - 9 A = 12

k equals 5.6

The equation does not have a solution.

Yes it is. The thing that makes it a quadratic equation is that "x squared" in there.